Yehor Redin in life and work (by letters to Volodymyr Savva). - Domanovska, Maryna; Hordiienko, Dmytro (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Research aim. Update of the scientific work and epistolary legacy of the famous scientist and specialist in art history, byzantinist, professor of the Kharkiv Imperial University Yehor Redin (1863–1908), publication and commenting of the scientist’s letters to his colleague Volodymyr Savva (1865–1920) from the collection of the Central State Historical Archive of Ukraine, Kyiv (CSHA of Ukraine). Research methodology. The basis of the work is a combination of comparative-historical and biographical methods, the involvement of philological commenting techniques, as well as adherence to modern principles of publishing sources of personal origin, in particular epistolary. Scientific novelty. Nine letters of Yehor Redin to his colleague Volodymyr Savva have been put into scientific circulation, which chronologically cover the period from 1897 to 1902. The epistolas contain both personal and professional sides, in particular, the beginning of the scientist’s work on his doctor dissertation; based on them in the introductory the article specified some facts of the scientific and personal biography of the scientist are prezented. The relevance. Yehor Redin’s scientific legacy continues to be the subject of attention of modern historians and art critics. Given the fact that the materials of the personal archive of Yegor Redin are stored mainly on the territory of the Russian Federation and will be inaccessible to Ukrainian researchers for a long time, the materials from the Kyiv archives are of particular importance. The study presents new facts of the scientist’s biography and publishes the mentioned nine letters of Yehor Redin to Volodymyr Savva.